Research on Pipeline Damage Imaging Technology Based on Ultrasonic Guided Waves - Jian He; Chen Zhou; Liang Yang; Xiaodan Sun (Shock and Vibration)
Pipeline structures are important structural components that cannot be replaced in actual engineering applications. Damage to a pipeline structure will create substantial safety hazards and economic losses in a project. Therefore, it is extremely important to study damaged pipeline structures. In this paper, L(0,2) mode guided waves are used to identify, locate, and image single and double defects in straight pipe structures. For the case where there is a single defect in the straight pipe section, the influence of different excitation frequencies on the reflection coefficient of L(0,2) modal guided wave is studied, and the optimal excitation frequency of L(0,2) guided wave is 70 kHz when single damage is determined. For the case of double defects in the straight pipe section, the double-defect size, the distance between the defects, and the relative defect positions are studied, and the influence of the defect recognition effect is analyzed. The propagation path of the ultrasonic guided wave in the double-defect pipe section is analyzed. Finally, the effectiveness of the three-point axial positioning method and damage imaging method is verified by the single-defect tube segment ultrasonic guided wave flaw detection experiment.